2002
DOI: 10.1002/sim.979
|View full text |Cite
|
Sign up to set email alerts
|

Potential of feature selection methods in heart rate variability analysis for the classification of different cardiovascular diseases

Abstract: In this study heart rate variability (HRV) analysis was applied to characterize patients suffering from coronary heart disease (CHD), dilated cardiomyopathy (DCM) and patients who had survived an acute myocardial infarction (MI). On the basis of several HRV parameters, an optimal discrimination between the different kinds of cardiovascular diseases and between the diseases and healthy controls (HC) was derived by feature selection and linear classification. For each task a small favourable subset of a set of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Other than heart disorders, the heart rate signals can be used for diagnosis of diseases like diabetic neuropathies, and depression [10,[12][13][14][15]. They are cheap and can be acquired from ECG signals.…”
Section: Introductionmentioning
confidence: 99%
“…Other than heart disorders, the heart rate signals can be used for diagnosis of diseases like diabetic neuropathies, and depression [10,[12][13][14][15]. They are cheap and can be acquired from ECG signals.…”
Section: Introductionmentioning
confidence: 99%
“…A powerful noninvasive tool that allows studying the autonomic cardiovascular modulation is the analysis of heart rate variability (HRV) [2123]. The reduction in HRV is strongly related to the severity of heart disease [24,25] and could have a reliable prognostic value for its clinical outcome [2429]. Furthermore, the study of DeAngelis et al [30] reported that alterations in autonomic modulation may be an initiating mechanism underlying the onset of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, non-linear analysis of Heart Rate Variability (HRV) has been used to characterize healthy people and a variety of heart diseases and different levels of risk [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…">IntroductionDuring recent years, non-linear analysis of Heart Rate Variability (HRV) has been used to characterize healthy people and a variety of heart diseases and different levels of risk [1][2][3][4][5].Different non-linear measures are used for this purpose, like Hurst and Lyapunov exponents, entropies, complexity and information indexes, symbolic logic and dimensional analysis. This latter one, estimates the dimension of the attractor formed by the set of points in the phase space, which is a statistical measure of the self similarity of the geometry of points and is related to the number of independent variables (degrees of freedom) needed to generate a corresponding process.…”
mentioning
confidence: 99%